2D radial-azimuthal particle-in-cell benchmark for E×B discharges. (1st July 2021) - Villafana, W; Petronio, F; Denig, A C; Jimenez, M J; Eremin, D; Garrigues, L; Taccogna, F; Alvarez-Laguna, A; Boeuf, J P; Bourdon, A; Chabert, P; Charoy, T; et al.
Abstract: In this paper we propose a representative simulation test-case of E × B discharges accounting for plasma wall interactions with the presence of both the electron cyclotron drift instability and the modified-two-stream-instability. Seven independently developed particle-in-cell (PIC) codes have simulated this benchmark case, with the same specified conditions. The characteristics of the different codes and computing times are given. Results show that both instabilities were captured in a similar fashion and good agreement between the different PIC codes is reported as main plasma parameters were closely related within a 5% interval. The number of macroparticles per cell was also varied and statistical convergence was reached. Detailed outputs are given in the supplementary data, to be used by other similar groups in the perspective of code verification.